Fine mapping of a QTL and identification of candidate genes associated with cold tolerance during germination in peanut (Arachis hypogaea L.) on chromosome B09 using whole genome re-sequencing - Zhang, Xin; Zhang, Xiaoji; Wang, Luhuan; Liu, Qimei; Liang, Yuying; Zhang, Jiayu; Xue, Yunyun; Tian, Yuexia; Zhang, Huiqi; Li, Na; Sheng, Cong; Nie, Pingping; et al. (Frontiers in Plant Science, 2023)
Low temperatures significantly affect the growth and yield of peanuts. Temperatures lower than 12 °C are generally detrimental for the germination of peanuts. The objective of this study was to investigate the genetic architecture underlying cold tolerance in peanuts during germination. For this purpose, we developed a recombinant inbred line (RIL) population comprising 807 RILs. Peanut accessions were measured for low-temperature germination under cold stress conditions. We constructed a high-density genetic map for peanuts and identified a major quantitative trait locus (QTL), qRGRB09, on chromosome B09. Cold tolerance-related QTLs were repeatedly detected in five environments, and the genetic distance was 6.01 cM (46.74 cM - 61.75 cM) after taking a union set. To further confirm that qRGRB09 was located on chromosome B09, we developed Kompetitive Allele Specific PCR (KASP) markers for the corresponding QTL regions. A regional QTL mapping analysis, which was conducted after taking the intersection of QTL intervals of all environments into account, confirmed that qRGRB09 was between the KASP markers, G22096 and G220967 (chrB09:155637831–155854093), and this region was 216.26 kb in size, wherein a total of 15 annotated genes were detected. This study illustrates the relevance of whole genome re-sequencing (WGRS)-based genetic maps for QTL mapping and KASP genotyping that facilitated QTL fine mapping of peanuts. The results of our study also provided useful information on the genetic architecture underlying cold tolerance during germination in peanuts, which in turn may be useful for those engaged in molecular studies as well as crop improvement in the cold-stressed environment.